2010
DOI: 10.1186/1756-8722-3-46
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR-15a and miR-214 in human pancreatic cancer

Abstract: BackgroundRecent reports indicate that microRNAs (miRNAs) play a critical role in malignancies. However, the role that miRNAs play in pancreatic cancer remains to be determined. The purpose of this study was to investigate aberrantly expressed miRNAs in pancreatic cancer tissues and demonstrate their roles in disease progression.ResultsWe detected the expression patterns of miRNAs in 10 pancreatic cancer tissues and their adjacent benign tissues by quantitative real time-PCR (qRT-PCR) and found that miR-15a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 32 publications
2
162
3
1
Order By: Relevance
“…Recent evidence has suggested that miRNAs may be involved in the progression of human cancer, since numerous miRNAs have been observed to be deregulated during tumorigenesis in humans (19). Previous studies have demonstrated that miR-214 is downregulated in cervical cancer and upregulated in human pancreatic cancer (20,21). The present study has demonstrated that the expression of miR-214 was downregulated in HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 63%
“…Recent evidence has suggested that miRNAs may be involved in the progression of human cancer, since numerous miRNAs have been observed to be deregulated during tumorigenesis in humans (19). Previous studies have demonstrated that miR-214 is downregulated in cervical cancer and upregulated in human pancreatic cancer (20,21). The present study has demonstrated that the expression of miR-214 was downregulated in HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 63%
“…It has been documented to be aberrantly expressed in many tumors including breast, cervical, hepablastoma, pancreatic and lung cancer (Yanaihara et al, 2006;Magrelli et al, 2009;Yang et al, 2009;Zhang et al, 2010Derfoul et al, 2011. Accumulating evidence indicated that miR-214 functions either as onco-gene or tumor suppressor gene in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-214 has been shown to be upregulated in ovarian cancer (18), gastric cancer (19), Sézary syndrome (20) and melanoma (15), while it has been shown to be downregulated in cervical cancer (21), pancreatic cancer (22) and hepatocellular carcinoma (23). A recent study found that the concentrations of miR-214 were significantly higher in the serum of breast cancer patients in contrast to healthy women (24).…”
Section: Introductionmentioning
confidence: 99%